Emerging practices in onboarding programs for PAs: Program content. Issue 9 (September 2020) - Sanchez, Mara; Anglin, Lorraine; Rana, Rachel; Butterfield, Rita; Everett, Christine M.; Morgan, Perri
ABSTRACT: Objective: Healthcare organizations are interested in creating onboarding programs to assist new PA and NP employees as they transition to practice settings. There is a need for information on what the ideal content and topic areas are for clinics to include in their onboarding programs. Methods: In 2018, we interviewed 13 administrators of onboarding programs. Interviews were transcribed and analyzed for themes by a team of researchers, with feedback from interviewees. Results: Eight content areas were identified and described in this paper: culture and values; goals and strategies; task proficiency; rules and policies; structure; working relationships; wellness; and navigation and politics. Conclusions: These common content areas may provide a starting point for organizations designing onboarding programs for their unique organizations.